4-3(x+2)=-5x-(x-1)

Simple and best practice solution for 4-3(x+2)=-5x-(x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4-3(x+2)=-5x-(x-1) equation:



4-3(x+2)=-5x-(x-1)
We move all terms to the left:
4-3(x+2)-(-5x-(x-1))=0
We multiply parentheses
-3x-(-5x-(x-1))-6+4=0
We calculate terms in parentheses: -(-5x-(x-1)), so:
-5x-(x-1)
We get rid of parentheses
-5x-x+1
We add all the numbers together, and all the variables
-6x+1
Back to the equation:
-(-6x+1)
We add all the numbers together, and all the variables
-3x-(-6x+1)-2=0
We get rid of parentheses
-3x+6x-1-2=0
We add all the numbers together, and all the variables
3x-3=0
We move all terms containing x to the left, all other terms to the right
3x=3
x=3/3
x=1

See similar equations:

| -6v-8(6v-1)=-2(v-4) | | 5=4/70s | | 5m-6=3m+4 | | 44x+27=44x+28 | | -6x=10-8x | | (x^2-3x-10)/(x+4)=0 | | -7(1-4n)=-147 | | 5x-11=-35-5 | | 100+(x-25)+x+(x-15)=540 | | 21x+147=168x+12 | | 6x+6-9x=-12 | | -2(2x+7)-2(2x+7)=-36 | | 71+30d=350+30d | | 32=48+24t-16t^2 | | 41.5=7p | | -6(4r+7)=-6r-6 | | x²-36=64 | | -10+5x+40=90 | | 6a3/4a=16 | | 9(y−2)−8y=4(y+3)−4(y−1) | | (2/3)x=(5/3)x+1 | | 3/5x-9=5/6 | | 43200-75x+125=45450-175x | | 9(x-1)=-2x+24 | | (x)(1)+(3)(.50)=(3+x)(.80) | | 8x-2=8+3x | | -3(7k+1)=165 | | -2(w+10=6w+12 | | 1/3x+2=1/5x+8/5 | | 3y=23-7 | | 16-3x+2-12=28 | | -6x+7=7+6x |

Equations solver categories